2017
DOI: 10.1002/slct.201701943
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Three-Dimensional-Ordered Mesoporous Cobalt Oxides for Selective Oxidation of Benzyl Alcohol

Abstract: Highly ordered mesoporous cobalt oxide catalysts were successfully synthesized by using cubically ordered mesoporous silica (KIT‐6) as template. The structural and textural properties were well characterized by X‐ray powder diffraction (XRD), scanning electron microscope (SEM), transmission electron microscope (TEM), N2 adsorption and desorption, and X‐ray photoelectron spectroscopy (XPS) techniques. The three‐dimensional mesoporous Co3O4 with a well‐defined three‐dimensional structure, high specific surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…The filtrate was concentrated on a rotavapor and the product was purified by silica gel column chromatography. The identity of all three monoterpenes was confirmed by 1 H and 13 C NMR analysis, IR spectroscopy, and comparison with published data [27,28]…”
Section: Isolation Of Rotundifolonesupporting
confidence: 55%
See 1 more Smart Citation
“…The filtrate was concentrated on a rotavapor and the product was purified by silica gel column chromatography. The identity of all three monoterpenes was confirmed by 1 H and 13 C NMR analysis, IR spectroscopy, and comparison with published data [27,28]…”
Section: Isolation Of Rotundifolonesupporting
confidence: 55%
“…After evaporation of the solvent under reduced pressure, the product was purified by column chromatography on silica gel. (−)-Perillyl aldehyde was prepared from (−)-perillyl alcohol by selective oxidation using pyridinium chlorochromate (PCC) as the oxidising agent and dry CH 2 Cl 2 as the solvent, according to the method described in [27]. In brief, to a solution of (−)-perillyl alcohol (59.21 mmol) in 462 mL of dry CH 2 Cl 2 , a solution of PCC (177.63 mmol) in CH 2 Cl 2 was slowly added.…”
Section: Isolation Of Rotundifolonementioning
confidence: 99%
“…Ordered mesoporous metal oxides have promising applications in many fields due to their structural regularity, adjustable pore size, and high specific surface area [13]. Up to now, many ordered mesoporous metal oxides such as Co 3 O 4 [35,36,37], TiO 2 [38,39], WO 3 [40,41], Al 2 O 3 [42,43,44], ZrO 2 [45,46,47], CeO 2 [48,49,50], NiO [51,52], Cr 2 O 3 [53,54], Sm 2 O 3 [55], In 2 O 3 [2,56], and UO 2 [57] have been successfully synthesized. Although some ordered mesoporous metal oxides have been successfully synthesized, the structural stability and thermal stability still demand further improvement.…”
Section: Types Of Ordered Mesoporous Materialsmentioning
confidence: 99%
“…[71] Highly ordered mesoporous Co 3 O 4 have been prepared by Li et al through silica-templating methods to obtain a catalyst with a high surface area compared to a commercial Co 3 O 4 sample and active in the oxidation of benzyl alcohol. [72] Gu et al reported a one-step template-free solvothermal method to synthesize recyclable hollow carbon-modified Fe 3 O 4 catalyst active in the oxidation of benzyl alcohol. [73] Mesoporous NiO/Bi 2 WO 6 nanocomposite has been synthesized by Pordel et al and found to be an efficient catalyst for the oxidation of primary and secondary benzylic alcohols under mild conditions.…”
Section: Oxide-based Catalystsmentioning
confidence: 99%